The Influence of Organizational Citizenship Behavior and Appreciation on Teacher Performance - Marlina, Ani; Kurniatun, Taufani Chusnul; Kurniady, Dedi Achmad (Universitas Nahdlatul Ulama Blitar, 2025)
This research examines the influence of Organizational Citizenship Behavior (OCB) and rewards on teacher performance in State Junior High Schools in Bojong District, Purwakarta Regency A quantitative approach with an ex post facto design was used, and research subjects were selected through purposive sampling OCB data were collected based on conscientiousness, altruism, civic virtue, courtesy, and sportsmanship, while reward data included task completion, authority, skill improvement, salary, allowances, and career advancement Data analysis was conducted using simple regression and Independent Sample t-test in SPSS The research results indicate that OCB and rewards significantly affect teacher performance both individually and simultaneously A combination of good organizational citizenship behavior and a fair reward system creates a supportive work environment, enhancing teacher motivation and dedication. This contributes to the improvement of the quality of education and students' literacy skills, reflecting the importance of both factors in human resource management strategies at schools.